Reintegration of cyber veterans: challenges and strategies for post-war transition - Virtanen, Toni; Lassfolk, Christina; Davydiuk, Andrii; Noorma, Mart (Frontiers in Psychology, 2024)
Battles in the cyber domain often lack visibility compared to the physical domain, which can lead to insufficient appreciation of its actors’ achievements by the general public and society. Nonetheless, it has become a crucial area of modern warfare in which cyber professionals defend the nation’s critical infrastructure, support other military operations and achieve military objectives that could not be attained in other domains. Although cyber combatants might not have as high a risk of injury or death as those on the front lines, they still can face traumatic events and suffer from the same types of issues after the war as any other veteran. Earlier studies on war veterans have shown they have elevated risks of mental health issues, substance use, social problems and financial difficulties which might push some individuals towards a path of crime. The cyber domain is also not limited by time or place, which has given rise to cyber volunteerism in which skilled individuals around the globe decide to assist their own country or friendly nations. This publication aims to identify the challenges cyber veterans might face when transitioning back to civilian life and develop appropriate strategies to facilitate their reintegration. It also raises the awareness of the hundreds of thousands of volunteers who can develop similar problems after the war. Without proper awareness, support and dialogue, some of these individuals can also drift towards harmful social implications such as cybercrime.